Systematic Literature Review: The Effect of the Problem-Based Learning Model on Creative Thinking Skills - Dedy Kurniadi; Nindy Nource Ganap; Indra Muda (ATRIA: Jurnal Multidisiplin Riset Ilmiah, 2025)
Creative thinking skills are essential competencies in 21st-century education, essential for addressing the ever-evolving complexity of social, technological, and economic issues. Modern education systems no longer emphasize solely the acquisition of knowledge but also emphasize students' ability to develop new ideas, solve problems innovatively, and generate valuable solutions. One learning model believed to be capable of developing these skills is Problem-Based Learning (PBL). This model places real-world problems as the starting point of learning, encouraging students to explore knowledge, analyze, and develop ideas creatively. This study aims to systematically analyze various research findings examining the effect of the Problem-Based Learning model on students' creative thinking skills. The method used is a Systematic Literature Review (SLR) by examining various scientific articles published in national and international journals over the past ten years. The article selection process is carried out through several stages: identification, screening, feasibility assessment, and inclusion based on specific criteria relevant to the research objectives. The results of the study indicate that most of the analyzed studies concluded that the application of the Problem-Based Learning model has a positive influence on improving students' creative thinking skills. This is evident in the improvement in creativity indicators such as fluency (fluency of ideas), flexibility (flexibility of thinking), originality (originality of ideas), and elaboration (development of ideas). Furthermore, PBL can also increase student engagement in the learning process, strengthen collaboration skills, and foster learning independence. The findings of this study imply that the application of Problem-Based Learning can be an effective learning strategy in developing creative thinking skills at various levels of education. Therefore, educators are advised to integrate problem-based learning models into the learning process systematically and contextually.